Primary intraosseous meningioma with subcutaneous and dural invasion: A case report and literature review - Zou, Mingang; Yang, Ruijin; Tang, Zhiji; Luo, Defang; Jiang, Qiuhua (Frontiers in Surgery, 2022)
Primary intraosseous meningiomas (PIOMs) are a rare subset of meningiomas, comprising fewer than 1% of all such tumors. Furthermore, PIOMs presenting as osteogenic lesions that invade both the dura and subcutaneous tissue are extremely rare. Unlike intracranial meningiomas, diagnosing and treating PIOMs are challenges due to their insidious clinical behavior and greater tendency for malignancy and a lack of clear radiological diagnostic criteria. We report the case of a 60-year-old female with headache and a slightly outward protrusion of the parietal region of the skull. CT showed an osteogenic lesion in the right parietal bone. MR imaging indicated mild to moderate homogeneous enhancement with an intense dural reaction. The suggested clinical diagnosis was lymphoma, so we performed a skull biopsy, which revealed an intraosseous benign meningioma. A precise resection strategy was planned with a neuronavigation system accompanied by a one-step customized titanium mesh cranioplasty. The lesion was completely removed, and pathological analysis confirmed a meningothelial meningioma (WHO Grade I) of intraosseous layer origin invading the dura mater and subcutaneous tissue. This case highlights the need for an initial biopsy and suggests that PIOMs may appear to be highly aggressive even if the histology is benign. Complete resection should be attempted to minimize the risk of recurrence.